Effects of peri-traumatic stress experienced during Hurricane Sandy on functional limitation trajectories for older men and women. (July 2021) - Pruchno, Rachel; Wilson-Genderson, Maureen; Heid, Allison R.; Cartwright, Francine P.
Abstract: Background and methods: Although the short-term effects of disasters on the physical health of mid-life and older people have been documented, little is understood about the long-term effects that disasters have on the physical health of these people. Based on the environmental docility hypothesis and research regarding gender effects on functional limitations and disaster, our analyses examined the effects of peri-traumatic stress experienced during Hurricane Sandy using longitudinal data from 5688 people aged 50 and older collected over six waves (2006–2019). Results: We found that functional limitations follow three trajectories, with people in each group having a significant linear increase over time and all but the highest functioning people also having a significant quadratic effect, indicating that the linear increase peaked post-Hurricane and then slowed in later waves. Conclusion: Consistent with the environmental docility hypothesis, peri-traumatic stress had its greatest impact on people with more functional limitations before the hurricane. Men experiencing peri-traumatic stress during Hurricane Sandy were more likely to experience an increase in functional limitations than women. These findings, which identify people most likely to experience long-term health effects following a disaster, can be used to inform health policies before, during, and after disaster strikes. Highlights: Study identified three trajectories of functional limitations. People with more functional limitations before the hurricane were at most risk. Men experienced a greater increase in functional limitations than women.